Epidemiological impact of HIV on second - line drug resistance in patients with multidrug resistant tuberculosis in high HIV prevalent settings in South Africa - Rheeder, Paul (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2014.